Preparation and use of food-based dietary guidelines : report of a joint FAO/WHO consultation (WHO, 1998)
This report provides an expert practical guide to the formulation and implementation of national dietary guidelines based on recommended foods and food groups rather than nutrients. Addressed to policy-makers and the nutritionists who advise them the report aims to facilitate the use of food-based dietary guidelines as a sensible new way to help consumers make healthy food choices. Throughout the report recommendations - whether concerning the importance of food variety or the percent of dietary protein that should be of animal origin - draw on the latest biochemical and physiological knowledge about human nutritional requirements in health and disease. Health problems related to both dietary insufficiency and excess are considered in this comprehensive report. The book opens with an explanation of the many reasons why dietary recommendations based on foods are more effective as an instrument of public health nutrition than are guidelines based on nutrients. Readers are also reminded of the need to formulate dietary guidelines in response to specific diet-related health problems important in a country, and to ensure that recommendations are based on sound scientific evidence. Against this background, the first main section establishes the scientific rationale for the development of food-based dietary guidelines, drawing on current knowledge in four main areas: nutrition science; food science and technology; educational, behavioural, and social sciences; and agricultural and environmental sciences. The section also compares different methods for assessing the nutritional quality of diets and explains each of the steps to follow when reorienting dietary recommendations from nutrients to foods. Methods of monitoring food and nutrient intake are presented and compared in the next section, which includes advice on how data from a range of sources can be used when setting dietary goals and formulating recommendations. Section three provides detailed, step-by-step guidance on how to develop food-based dietary guidelines and ensure that populations understand them and follow their advice. The remaining sections explain how to transform guidelines into message and slogans and monitor their effectiveness in improving dietary practices. In a key achievement, the second part of the report provides an expert state-of-the-art review of scientific knowledge, from animal, clinical, and epidemiological studies, about the relationship between diet, nutrition and health. Throughout this review, a special effort is made to identify areas where scientific data support firm dietary recommendations based on individual foods, food groups, and food combinations. Information ranges from advice on the use of nutrient densities in the development and evaluation of dietary guidelines, through data on the role of vitamins as chemopreventive agents, to a discussion of non-nutrient components found in fruit that may explain their capacity to prevent cardiovascular diseases and gastrointestinal cancers. The report concludes with examples of the ways in which foods and food groups have been incorporated into dietary guidelines in selected countries.
WHO technical report series, ISSN 0512-3054 880
Keywords: Nutritional Requirements; zemědělství a potravinářství; dieta; směrnice jako téma; hodnocení stavu výživy; Diet; Nutrition Assessment; Guidelines as Topic; nutriční nároky; Eating; přijímání potravy; nutriční terapie, dietoterapie a výživa